Sex Differences in Nonalcoholic Fatty Liver Disease: State of the Art and Identification of Research Gaps. Issue 4 (23rd September 2019) - Lonardo, Amedeo; Nascimbeni, Fabio; Ballestri, Stefano; Fairweather, DeLisa; Win, Sanda; Than, Tin A.; Abdelmalek, Manal F.; Suzuki, Ayako
Abstract : Despite tremendous research advancements in nonalcoholic fatty liver disease (NAFLD), our understanding of sex differences in NAFLD remains insufficient. This review summarizes the current knowledge on sex differences in NAFLD, identifies gaps, and discusses important considerations for future research. The prevalence and severity of NAFLD are higher in men than in women during the reproductive age. However, after menopause, NAFLD occurs at a higher rate in women, suggesting that estrogen is protective. Sex differences also exist for the major risk factors of NAFLD. In general, animal models of NAFLD recapitulate the sex differences observed in patients, with more severe steatosis and steatohepatitis, more proinflammatory/profibrotic cytokines, and a higher incidence of hepatic tumors in male than female subjects. Based on computer modeling, female and male livers are metabolically distinct with unique regulators modulating sex‐specific metabolic outcomes. Analysis of the literature reveals that most published clinical and epidemiological studies fail to examine sex differences appropriately. Considering the paucity of data on sex differences and the knowledge that regulators of pathways relevant to current therapeutic targets for NAFLD differ by sex, clinical trials should be designed to test drug efficacy and safety according to sex, age, reproductive stage (i.e., menopause), and synthetic hormone use. Conclusion: Sex differences do exist in the prevalence, risk factors, fibrosis, and clinical outcomes of NAFLD, suggesting that, while not yet incorporated, sex will probably be considered in future practice guidelines; adequate consideration of sex differences, sex hormones/menopausal status, age, and other reproductive information in clinical investigation and gene association studies of NAFLD are needed to fill current gaps and implement precision medicine for patients with NAFLD.